Programming iOS 8 - Neuburg, Matt, ....- (Beijing : O'Reilly Media, 2014)
Start building apps for iOS 8 with Apple's Swift programming language. If you're grounded in the basics of Xcode and the Cocoa framework, this book provides a structured explanation of all essential real-world iOS app components. Through deep exploration and copious code examples, you'll learn how to create views, manipulate view controllers, and use iOS frameworks for adding features such as audio and video, access to user calendars and photos, and tracking the device's location.